The effect of clinical setting on the unstimulated salivary flow rate. (September 2016) - Varoni, Elena Maria; Federighi, Veronica; Decani, Sem; Carrassi, Antonio; Lodi, Giovanni; Sardella, Andrea
Highlights: Clinical setting does not influence unstimulated salivary flow rate. UWS sialometry is excellent for the accurate evaluation of salivary flow rate. UWS sialometry is prone to physiological variations over time. Abstract: Objective: Unstimulated whole saliva (UWS) sialometry uses the spitting method to assess occurrence of hyposalivation. This study compares the UWS flow rates in volunteers sitting in a laboratory or in a clinical setting, in order to evaluate the influence of environment on salivary secretion. Design: 25 healthy volunteers were recruited and divided into two groups to perform UWS sialometry under the two different settings (T1). Eleven weeks later, the participants repeated the same test (T2). At a unique time point and under the clinical setting, 18 patients complaining of xerostomia also performed the UWS sialometry; these values were used as control to corroborate findings. Results: Different scenarios – laboratory one vs. clinical one – did not affect measurements of mean UWS flow rates. Both intra- and inter-individual variabilities, reported as standard error of the mean (SEM) and within-subject variance (WSV), resulted below the threshold of 0.1 g/min. A significant difference was found between UWS flow rates from healthy volunteers and those from patients with xerostomia ( p  < 0.05). Test/retest reliability showed a moderate correlation of datasets collected at the two time points from healthy volunteers (T1 vs. T2, 11 weeks later): under laboratory and clinical settings, Pearson's coefficients of correlation were r = 0.62 and r = 0.32, respectively. Conclusions: Type of environment did not influence UWS sialometry via spitting method, which appeared reliable for intra-day analysis of the salivary flow rate, although prone to physiological variations over time.